Pengaruh Irigasi dan Mulsa Kulit Singkong Terhadap Kadar Air Tanah serta Pertumbuhan Tanaman Nanas - Ali Rahmat; - Afandi; Tumiar K Manik; Priyo Cahyono (Balai Teknik Irigasi, 2013)
Irrigation on pineapple plants is very important because it affects the growth and production, but the irrigation cost is very expensive. The study aimed to determine the effect of irrigation and organic mulch on soil moisture content and pineapple growth. The study was conducted with a factorial treatment design (5 x 2) in a randomized block design with three replications. The first factor is the time length of irrigation (I), which consists of 5 time irrigation i.e. without irrigation (I0), irrigated 1 month (I1), irrigated 2 months (I2), irrigated 3 months (I3), and irrigated 4 months (I4). The second factor is the dose of cassava peel (organic mulch) consists of 2 level is 0 ton/ha (M0) and 50 ton/ha (M1). Soil moisture was measured using diviner 2000. Data of soil moisture content were analyzed on time series. Plant growth performance were analyzed and tested with LSD at 5% level. The results showed cassava peel of 50 ton/ha in general could last 2.5 months to maintain higher water content. Cassava peel had more visible role when the soil begins to dry. Cassava peel effected height and fresh weight of the plant. And, irrigation effected on fresh weight of the plant. The interaction between irrigation and cassava peel affected on the fresh weight of the plant. Crop recovery occurred after the rainy season where the soil moisture was high.